Psychological Distress, Anxiety, and Academic Self-Efficacy as Predictors of Study Satisfaction Among Peruvian University Students During the COVID-19 Pandemic - Carranza Esteban, Renzo Felipe; Mamani-Benito, Oscar; Caycho-Rodriguez, Tomás; Lingán-Huamán, Susana K.; Ruiz Mamani, Percy G. (Frontiers in Psychology, 2022)
The objective of this research study was to determine if psychological distress, anxiety, and academic self-efficacy predict satisfaction with studies in Peruvian university students during the COVID-19 pandemic. A cross-sectional and predictive design was used, in which 582 Peruvian university students participated, 243 men and 339 women, between the ages of 16 and 41. Student’s t-statistics were used to analyze the differences in scores of psychological distress, anxiety, academic self-efficacy, and satisfaction with studies based on the sex of the participants, Pearson’s R was used for the analysis of correlations between variables, and multiple linear regressions were used to evaluate the predictive model. In the analyses, the significance level was set at 0.05. The results show that men have higher levels of psychological distress, anxiety, and academic self-efficacy than women do (p < 0.01); high levels of psychological distress correlate with high levels of anxiety (r = 0.580, p < 0.01) and low levels of satisfaction with studies (r = –0.178, p < 0.01) and academic self-efficacy (r = −0.348, p < 0.01); high levels of anxiety correlate with low levels of satisfaction with studies (r = −0.122, p < 0.01) and academic self-efficacy (r = –0.192, p < 0.01); and high levels of academic self-efficacy correlate with high levels of satisfaction with studies (r = 0.429, p < 0.01). Academic self-efficacy was also found to predict satisfaction with studies (β = 0.429, p < 0.01). This concludes that, although there are significant correlations between psychological distress, anxiety, academic self-efficacy, and satisfaction with studies, academic self-efficacy is the variable that most predicts satisfaction with studies in Peruvian university students.